Proarrhythmic Electrical Remodeling by Noncardiomyocytes at Interfaces With Cardiomyocytes Under Oxidative Stress - Zhao, Yali; Iyer, Shankar; Tavanaei, Maryam; Nguyen, Nicole T.; Lin, Andrew; Nguyen, Thao P. (Frontiers in Physiology, 2021)
Life-threatening ventricular arrhythmias, typically arising from interfaces between fibrosis and surviving cardiomyocytes, are feared sequela of structurally remodeled hearts under oxidative stress. Incomplete understanding of the proarrhythmic electrical remodeling by fibrosis limits the development of novel antiarrhythmic strategies. To define the mechanistic determinants of the proarrhythmia in electrical crosstalk between cardiomyocytes and noncardiomyocytes, we developed a novel in-vitro model of interface between neonatal rat ventricular cardiomyocytes (NRVM) and controls (NRVMs or connexin43 (Cx43)-deficient HeLa cells) vs Cx43+ noncardiomyocytes (aged rat ventricular myofibroblasts (ARVF) or HeLaCx43 cells). We performed high-speed voltage-sensitive optical imaging at baseline and following acute H2O2 exposure. In NRVM-NRVM and NRVM-HeLa controls, no arrhythmias occurred under either experimental condition. In the NRVM-ARVF and NRVM-HeLaCx43 groups, Cx43+ noncardiomyocytes enabled passive decremental propagation of electrical impulses and impaired NRVM activation and repolarization, thereby slowing conduction and prolonging action potential duration. Following H2O2 exposure, arrhythmia triggers, automaticity, nonreentrant, and reentrant arrhythmias emerged. This study reveals that myofibroblasts (which generate cardiac fibrosis) and other noncardiomyocytes can induce not only structural remodeling but also electrical remodeling and that electrical remodeling by noncardiomyocytes can be particularly arrhythmogenic in the presence of an oxidative burst. Synergistic electrical remodeling between H2O2 and noncardiomyocytes may account for the clinical arrhythmogenicity of myofibroblasts at fibrotic interfaces with cardiomyocytes in ischemic/non-ischemic cardiomyopathies. Understanding the enhanced arrhythmogenicity of synergistic electrical remodeling by H2O2 and noncardiomyocytes may guide novel safe-by-design antiarrhythmic strategies for next-generation iatrogenic interfaces between surviving native cardiomyocytes and exogenous stem cells or engineered tissues in cardiac regenerative therapies.